Analysis Concept of The Blue Economy Islamic Perspective (Case studi Jumiang as Marine Tourism in Pamekasan) - Fahrurrozi Fahrurrozi (Perisai : Islamic Banking and Finance Journal, 2020)
Jumiang Beach is an interesting marine tourism destination in Pamekasan, Madura. This makes it possible to both improve the quality of environment and enhance local society’s economic life. On the other hand, a bad effect of tourims affects environment due to the bad deed of local people and visitors in expoliting natural resource improperly. The problem of rubbish also takes concern. Through the principle of Blue Economy, the enhancement of ability, innovation and creativity is put into a wish to efficiently boost the use of natural tourism resource. Islam is a comprehensive religoin that it covers every single aspect of life, including the concept of blue economy. The concept is based on some principles including creativity, innovation, local resource use, and the use of recycleable materials into the better management of natural resource. Implementation of the concept is taken from the activities of marine society of Tanjung village at the Jumiang beach consisting of 1) The efficient use of natural resource is through Low CO2 Emission and resources efficient 2) Zero – Waste which leaves no rubbish at all 3) Social solidarity in empowering local people including program socialization, people resuscitation, skill training, community development and so forth. 4) Multiple Revenue in which a person could earn from various occupation.